Membangun Karakter Demokratis Melalui Pendidikan Pancasila dan Kewarganegaraan di Sekolah - Ade Fadly Anugrah; Feronica Manurung; Habibi Habibi; Novita Rahayu; Ruth Clarissa Tambunan; Hamdi Abdullah Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2025)
Pancasila and Citizenship Education (PPKn) has a strategic role in building democratic character among the younger generation as an important capital in the life of society, nation and state. This research aims to analyze how the implementation of PPKn education in schools can be an effective means of internalizing democratic values, such as tolerance, justice, respect for human rights, and deliberation. Civics learning requires good preparation, especially through preparing material that not only provides knowledge but is also able to bring about changes in the character of students. This research uses a qualitative approach with a literature review method, which includes critical analysis of various sources, such as national and international journal articles, books, e-books, dissertations, theses, as well as print and online media which can provide a comprehensive picture of the role of PPKn in form students' democratic character. The research results show that PPKn education based on Pancasila values ​​has proven to be effective in developing individuals who have strong character and are able to face the challenges of the era of globalization. By combining the values ​​of Pancasila and democratic principles, this education plays a role in forming a highly civilized, competitive and globally superior nation.